If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 96 = 6(-2 + 3x) 96 = (-2 * 6 + 3x * 6) 96 = (-12 + 18x) Solving 96 = -12 + 18x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18x' to each side of the equation. 96 + -18x = -12 + 18x + -18x Combine like terms: 18x + -18x = 0 96 + -18x = -12 + 0 96 + -18x = -12 Add '-96' to each side of the equation. 96 + -96 + -18x = -12 + -96 Combine like terms: 96 + -96 = 0 0 + -18x = -12 + -96 -18x = -12 + -96 Combine like terms: -12 + -96 = -108 -18x = -108 Divide each side by '-18'. x = 6 Simplifying x = 6
| 30=21-2 | | 66=-6(-a-6) | | 4m+6t=15 | | 38=5-3h | | s^2+11s+30=0 | | 6(a+6)=72 | | 4x^3-9x^2+4=0 | | 8a+a=9 | | x^2+4x=-8 | | 12=k+3+7 | | 2x+3(x-4)=8 | | 5(1-3r)=65 | | 3t(4t-3)(3t-1)=0 | | 70=2(-1+6x) | | k=(30+3a)-(15-3a) | | -24=-2n-4n | | 10-7x=42-21x | | X+2+4=9 | | -94-9x=7x+18 | | x^2+kx+0.765625=0 | | (4b-20)(20b-4)=0 | | 192=16x | | 5x+11=-28-8x | | B-8=-21 | | 20n+6+5n-12+x+20= | | 4=20+r | | -16-2x=14-17x | | -16-2x=14-17x | | -104=-8x | | (5t-30)(30t-5)=0 | | X+(-1)=11 | | 9y-12=5y |